Strengthening Character Through Comparative Rhetoric and Istifham: A Study on E. Abdurrahman’s Thoughts on Character Education - Roni Nugraha; Joyce Bulan Basrawi; Adudin Adudin Alijaya (UIN Sunan Gunung Djati Bandung, 2024)
This article examines the Strengthening of Character through Comparative Rhetoric and Istifham (Rhetorical Questions): A Study of E. Abdurrahman’s Thoughts on Moral Education. As a second-generation activist of the PERSIS organization, besides being proficient in the field of fiqh, E. Abdurrahman demonstrated significant attention to moral education. He published at least 87 articles on moral education in various Islamic magazines between 1936 and 1983. The findings of this study indicate three key principles of moral education: moral education should be elevated from mere ability (bisa) to habitual practice (biasa); it must culminate in loyalty to God; and it should be student-centered, grounded in the philosophy of ngajeujeuhkeun. The concepts of